Education and Energy Consumption: a Provincial Analysis in Indonesia - Nadira Aisha Susanto; Djoni Hartono; Misdawita Misdawita; Didi Nuryadin; Ida Bagus Putu Cesario Putra Surayuda; Novani Karina Saputri; Shofie Azzahrah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2023)
The global and national energy consumption continues to increase every year, leading to increased carbon emissions. Households are one of Indonesia's energy consumers, where household members' educational level is considered to influence energy consumption. Due to the limited studies in Indonesia regarding the relationship between education and energy consumption, this study aims to explain the relationship between education and energy consumption among provinces in Indonesia. This study is a quantitative study under the STIRPAT framework, using three estimation methods to examine the impact of education on energy consumption among provinces in Indonesia from 2010 to 2021, namely OLS, Fixed Effect, and Fixed Effect Discroll-Kraay. The research was conducted with three different data analyses: Indonesia as a whole, Java, and non-Java regions. The study found differences in estimation results between Java and non-Java regions, providing evidence that the level of education has different associations with per capita energy consumption in these two areas. It was also found that the estimation results for Indonesia align with those in non-Java regions. The study concludes that education has a significant positive association with energy consumption in Indonesia and specifically in non-Java regions, while the association between education and energy consumption in Java is negative and significant. The policy implications suggest that the government should continue efforts to improve the quality of education and promote more efficient energy consumption education in the Java region and implement complementary policies such as compulsory education programs for non-Java regions to reduce energy consumption in Indonesia.